Self-Concept With Cross-Cultural Perspective: 36–72-Month-Old Preschool Children in Turkey and Germany - Celikel, Busra; Çoban, Aysel E. (Frontiers in Psychology, 2022)
Children attending preschool education in Turkey and Germany have different cultural environments and education systems. This study aimed at investigating the self-concept of 36–72- month-old preschool children in Turkey, a country with a collectivist culture, and Germany, a country with an individualistic culture. Participants were 433 children (234 female, 199 male) from Turkey and 206 children (102 female, 109 male) from Germany. Three dimensions of self-concept were measured: ability-based, social, and physical. The Self-Concept Questionnaire for Children (Preschool Version) was used for data collection. This process lasted about 5 months. Country (Turkey vs. Germany) and sex (male vs. female) of the child were analyzed as independent variables, and the three dimensions of self-concept (i.e., ability-based, social, and physical) were analyzed as dependent variables. As normality assumption was not met for the subgroups, the Mann–Whitney U test was applied for statistical analysis. Results showed significant differences between children from Turkey and children from Germany in two self-concept dimensions (i.e., ability-based and physical). It was determined that there were no differences between the two countries in social self-concept. It was also determined that there were differences in the ability-based self-concept dimension in 36–72-month-old children depending on gender in Turkey, in favor of male children. On the other hand, it was determined that there were no differences depending on gender in any of the self-concept dimensions in Germany. It was concluded that culture was a factor leading to differentiation in some dimensions of preschool children’s self-concept.